Ca(2+)-regulatory function of the inhibitory peptide region of cardiac troponin I is aided by the C-terminus of cardiac troponin T: Effects of familial hypertrophic cardiomyopathy mutations cTnI R145G and cTnT R278C, alone and in combination, on filament sliding - Brunet, Nicolas M. (2014)
Investigations of cardiomyopathy mutations in Ca(2+) regulatory proteins troponin and tropomyosin provide crucial information about cardiac disease mechanisms, and also provide insights into functional domains in the affected polypeptides. Hypertrophic cardiomyopathy-associated mutations TnI R145G, located within the inhibitory peptide (Ip) of human cardiac troponin I (hcTnI), and TnT R278C, located immediately C-terminal to the IT arm in human cardiac troponin T (hcTnT), share some remarkable features: structurally, biochemically, and pathologically. Using bioinformatics, we find compelling evidence that TnI and TnT, and more specifically the affected regions of hcTnI and hcTnT, may be related not just structurally but also evolutionarily. To test for functional interactions of these mutations on Ca(2+)-regulation, we generated and characterized Tn complexes containing either mutation alone, or both mutations simultaneously. The most important results from in vitro motility assays (varying [Ca(2+)], temperature or HMM density) show that the TnT mutant “rescued” some deleterious effects of the TnI mutant at high Ca(2+), but exacerbated the loss of function, i.e., switching off the actomyosin interaction, at low Ca(2+). Taken together, our experimental results suggest that the C-terminus of cTnT aids Ca(2+)-regulatory function of cTnI I(p) within the troponin complex.